Impact of propolis as a natural antibiotic on diet digestibility, purine derivatives, methane emission and blood constitutes of late pregnant ewes - Morsy A.S.; Soltan Y.A.; El-Zaiat H.M.; Abdalla A.L. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Antibiotic are widely used in ruminant nutrition as feed additives to improve growth energy, protein utilization and decrease methane (CH4) emissions. However, there is a controversy about the use of such additives because of the risk of transferring residues into meat and milk and development of resistant strains of bacteria. These concerns have promoted the search for alternative natural feed additives, such as propolis. Eighteen ewes were individually allotted to indoor pens to study the impact of propolis as a natural antibiotic on diet digestibility, purine derivatives, CH4 emissions and blood constitutes of late pregnant Santa Inês ewes. The study lasted for 43 day and ewes were assigned to a randomized complete block design with 9 blocks and 2 dietary treatments as follows: Control (CTL) without propolis administration and propolis (BRP) received 3 g red propolis extract /ewe/day. Intake of N and body N retention increased (p < 0.05) for BRP supplementation than CTL expressed as g / animal / day. The administration of BRP increased (P < 0.05) urinary allantoin compared to the CTL. BRP supplementation increased (P < 0.05) OM and CP digestibility compared to the CTL. Additionally BRP decreased (P < 0.05) CH4 emission expressed as L/day or L/kg for (OMI and DOM) when compared to CTL group. Propolis increased (P < 0.05) all hematological parameters moreover the same pattern was observed for the biochemical parameters too. Propolis supplementation resulted in decrease (P < 0.05) cortisol, T3 and T4 compared to CTL. Propolis represents a promising natural antibiotic with profit biological and environmental effects.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)